based on the zero product property which of the following statements must be true about the quadratic equation (3x+4)(x-2)=0

1 answer

The zero product property states that if the product of two expressions equals zero, then at least one of the expressions must be equal to zero.

For the quadratic equation given, \((3x + 4)(x - 2) = 0\), we can apply the zero product property. This means:

  1. \(3x + 4 = 0\) or
  2. \(x - 2 = 0\)

Now, let’s solve each equation:

  1. For \(3x + 4 = 0\): \[ 3x = -4 \ x = -\frac{4}{3} \]

  2. For \(x - 2 = 0\): \[ x = 2 \]

So, the solutions to the equation \((3x + 4)(x - 2) = 0\) are \(x = -\frac{4}{3}\) and \(x = 2\).

Therefore, the statements that must be true about the quadratic equation are:

  • \(x = -\frac{4}{3}\) is a solution.
  • \(x = 2\) is a solution.

In conclusion, the solutions of the equation \( (3x + 4)(x - 2) = 0 \) are \(x = -\frac{4}{3}\) and \(x = 2\).

Similar Questions
  1. The zero product property quick checkBased on the Zero Product Property, which of the following statements must be true about
    1. answers icon 1 answer
    1. answers icon 3 answers
  2. The Zero Product Property Quick Check2 of 52 of 5 Items Question Based on the Zero Product Property, which of the following
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions